2015
DOI: 10.1039/c5py01332a
|View full text |Cite
|
Sign up to set email alerts
|

Direct copolycondensation of biobased elastomers based on lactic acid with tunable and versatile properties

Abstract: Tunable and versatile biobased copolyesters with excellent performances in nanocomposites, polylactide tougheners and shape memory were synthesized and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 40 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…PBS has a global capacity of over 140,000 t/a, which was 12.8% of global capacity of biobased degradable plastics reported in 2014 (Hu et al., 2015, 2019). Commercially available PBS and PBSA products include GSPLA ® (Mitsubishi Chemicals), Bionolle™ (Showa Denko K.K.…”
Section: Synthetic Biobased Biodegradable Polymers For Food Packagingmentioning
confidence: 92%
“…PBS has a global capacity of over 140,000 t/a, which was 12.8% of global capacity of biobased degradable plastics reported in 2014 (Hu et al., 2015, 2019). Commercially available PBS and PBSA products include GSPLA ® (Mitsubishi Chemicals), Bionolle™ (Showa Denko K.K.…”
Section: Synthetic Biobased Biodegradable Polymers For Food Packagingmentioning
confidence: 92%
“…13 Hu et al 14 synthesized a series of crosslinkable linear biobased elastomer composites with high strength and elasticity based on lactic acid, which are promising for engineering and medical applications. 13 Hu et al 14 synthesized a series of crosslinkable linear biobased elastomer composites with high strength and elasticity based on lactic acid, which are promising for engineering and medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…This type of intervention emphasizes more opportunities to use POS in neighborhoods [37]. Many studies have shown a positive association between creating POS and green spaces and mental health bene ts [3,[39][40][41][42]. According to the quality of neighborhoods on the older people's mental health [40], improving the neighborhood's characteristics can lead to the social integration of older residents and higher social interactions [42][43][44].…”
Section: Discussionmentioning
confidence: 99%